METODE MENGHAFAL AL-QUR’AN UNTUK ANAK USIA DINI DI RUMAH TAHFIDZ SOFWAN SALIM PALEMBANG - Yuantini, Gustiana; Kibtiyah, Meriyatul (Program Studi Pendidikan Islam Anak Usia Dini, 2021)
This study aims to describe the method memorizing the Qur’an applied tahfidz Sofwan Salim Palembang. This research uses descriptive method with is a kiand of qualitative approach. The research subject is the tahfidz progran teacher and the research informants are supervisor and students. Data collection using observation method, interviews and documentation. The result of this study fount data on the method of memorizing the Qur’an applied in the tahfidz Qur’an Sofwan Salim Palemabang the Tallaqi method. The supporting factor in memorizing the Qur'an is the enthusiasm of early childhood students in memorizing the Qur'an is quite good, This can be proven by the presence of students who are always on time and their enthusiasm when listening to the material. While the inhibiting factor is long and short reading, the pronunciation of makhraj is still not clear and early childhood students have a very short concentration range so they get bored easily and play with their friends. There are several efforts made by the student mentors so that learning to memorize the Koran is easier and more enjoyable. Before starting the lesson all tahfidz quran students are required to repeat memorization or murojaah from the 30th Juz (An-Naba's letter etc.) together. Tahfidz house supervisor Sofwan Salim did not apply memorization targets for the students so as not to make the students burdened when they came to the Tahfidz house.